(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2018)
Review of the three-volumes reliable and meticulous edition of La media noche by Ramón del Valle-Inclánis edited by Bénedicte Vauthier and Margarita Santos Zas and published by the Universidade de Santiago de Compostela(Cátedra Valle-Inclán) in cooperation with the Grupo de Investigación Valle-Inclán-USC (2017).